Stakeholder Perceptions of the Impact of Artificial Reef Deployment: A Case Study of the Indonesian Coral Reef Garden (ICRG) in Nusa Dua, Bali - Yulius, Yulius; Tito, Camellia; Ramdhan, Muhammad; Purbani, Dini; Arifin, Taslim; Setyawidati, Nur A.R.; Kusuma, Luh P A Savitri C Kusuma; Sabina, Anninda (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
This research examines the challenges of coral reef conservation in Bali, a critical hub for marine tourism. Despite the island’s global significance, efforts to preserve its coral reefs have been insufficient, leading to the launch of the 2020 Integrated Coral Reef Rehabilitation and Management Program (ICRG). Supported by National Economic Recovery (PEN) funds, the ICRG has focused on deploying artificial reefs in the waters of Nusa Dua. However, only 74.3 hectares of the potential 204 hectares of restoration areas have been addressed, underscoring the need for more intensive conservation efforts. Data collection involved the distribution of closed questionnaires to key stakeholders, including government bodies, academic institutions, tourists, and coral reef conservation organizations. The data was analyzed using both descriptive statistics and thematic analysis to gauge stakeholder awareness, perceptions, and willingness to contribute to conservation efforts. The analysis revealed that 69% of respondents have a comprehensive understanding of the ecological, economic, and social functions of coral reefs. Furthermore, 92% of respondents expressed a willingness to contribute to coral reef preservation, either through labor or financial means. Financial contributions ranged from Rp. 25,000 to Rp. 150,000, with 30% of respondents willing to allocate up to 5% of their annual income to conservation initiatives. These findings highlight a strong stakeholder commitment to coral reef conservation in Bali and emphasize the necessity for ongoing public engagement and support. The research suggests that integrating local customary laws into conservation strategies and enhancing public involvement could significantly bolster the long-term sustainability of coral reef restoration efforts in Bali, thereby preserving the island’s marine tourism appeal and ecological integrity.